1999
DOI: 10.3904/kjim.1999.14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection on antral gastrin and somatostatin cells and on serum gastrin concentrations

Abstract: ObjectivesHelicobacter pylori infection induces selective reduction of the number of antral D-cells and results in abnormal regulation of serum gastrin secretion. The purpose of this study was to investigate the relationship between H. pylori infection and the numbers of G-cells and D-cells.MethodsThe numbers of antral G-cells and D-cells, the ratio of G-cells to D-cells and fasting serum gastrin concentrations were compared between 37 patients with (29 with duodenal ulcers and 8 with gastric ulcers) and 33 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(27 reference statements)
2
8
1
Order By: Relevance
“…A significant benefit of combined therapy on IL-4 more profound than single therapy alone suggested that combined therapy could reduce the effects of H. pylori infection more than each therapy alone. Gastrin is a hormone produced by G cells from the antrum and involved in the production of gastric acid [33]. Similar to current result, it is clear the levels of gastrin and gastric acid were increased by H. pylori infection.…”
Section: Discussionsupporting
confidence: 79%
“…A significant benefit of combined therapy on IL-4 more profound than single therapy alone suggested that combined therapy could reduce the effects of H. pylori infection more than each therapy alone. Gastrin is a hormone produced by G cells from the antrum and involved in the production of gastric acid [33]. Similar to current result, it is clear the levels of gastrin and gastric acid were increased by H. pylori infection.…”
Section: Discussionsupporting
confidence: 79%
“…The G cell-to-D cell ratio obtained from our immunohistochemistry analysis is similar to G cell-to-D cell ratios reported previously (26). Experimental evidence suggests that there are Ͻ10 of each endocrine cell type per gastric gland (26,77); therefore, the three-dimensional analysis used to estimate corpus D and parietal cells is not needed to estimate the numbers of antral cells. To deduce the number of G and D cells in the antrum, we assume that the antrum comprises 25% of the stomach, and, given the total number of gastric glands in the stomach (31), we calculate the number of each of the antral cell types (Table 1).…”
Section: Methodssupporting
confidence: 84%
“…In Sheykholeslami et al, study, Gastrin-17 was increased in corpus-predominant gastritis (p < 0.01) [5]. However in this study, Gastrin-17 level was significantly higher in severe neutrophil infiltration.…”
Section: Discussioncontrasting
confidence: 58%